The sensitivity of different environments to radioactive contamination - Monte, L. (Journal of Environmental Radioactivity, 2013)
This paper describes modelling calculations carried out to determine the sensitivity of various rural and semi-natural environments to radionuclide contamination by 137Cs, 90Sr, and 131I released during a major nuclear accident. Depositions of 1000 Bq/m3 were assumed for each radionuclide. Four broad types of environments were considered: agricultural, forest or tundra, freshwater aquatic, and coastal marine. A number of different models were applied to each environment. The annual dose to a human population receiving most or all of its food and drinking water from a given environment was taken as a broad measure of sensitivity. The results demonstrated that environmental sensitivity was highly radionuclide specific, with 137Cs generally giving the highest doses during the first year, especially for adults, in terrestrial and freshwater pathways. However, in coastal marine environments, 131I and 239Pu were more significant. Sensitivity was time dependent with doses for the first year dominating those for the 2nd and 10th years after deposition. In agricultural environments the ingestion dose from 137Cs was higher for adults than other age groups, whereas for 90Sr and 131I, the ingestion dose was highest for infants. The dependence of sensitivity on social and economic factors such as individual living habits, food consumption preferences, and agricultural practices is discussed. © 2013 Elsevier Ltd.